PENGARUH PEMBERIAN BIOCHAR DAN PESTISIDA BERBAHAN CHITOSAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BROKOLI (Brassica oleraceae var. Italica) - Triana, Hesti; Alfian, Rizki; Damung, Yovita Mariana; Fikrinda, Wahyu (Universitas Tribhuwana Tunggadewi, 2023)
This research aimed to determine the effect of applying biochar and chitosan-based pesticides on the growth and production of broccoli plants. This research used a factorial randomized block design. The first factor, namely biochar, consists of 4 (four) levels; B0: control, B1: 160 g/polybag, B2: 320 g/polybag, and B3: 480 g/polybag. The second factor, namely chitosan, consists of 3 (three) levels; C0: control, C1: 1.5 ml/l water, and C2: 3 ml/l water. Data analysis used analysis of variance (ANOVA) and further testing using BNT at the 5% level. The results showed that there was no interaction between giving biochar and chitosan on broccoli growth and yield parameters, but separately giving biochar had a significant effect on plant height, number of leaves, leaf area, flower diameter, flower weight, and production yield, chitosan treatment had a significant effect on plant height, number of leaves, leaf area, flowering age, flower diameter, flower weight, wet and dry weight of stover, and production yield. The best biochar treatment was at a dose of 480 g/polybag (B3) with a production yield of 12.69 t/ha compared to the control 11.49 t/ha and the best chitosan treatment was at a dose of 3 ml/l water (C2) with a production yield of 12 .82 t/ha compared to the control, namely 11.09 t/ha. The application of 160 g biochar/polybag + 3 ml chitosan/l showed that it was able to suppress the development of black rot disease with a disease incidence percentage of 0-8% compared to the control of 8-50% and a wound diameter on flowers of 0.00 cm compared to controls of 1.87 cm.